Exercise Training Modalities in Young and Middle‐Aged Adults With Prehypertension or Hypertension: A Systematic Review and Network Meta‐Analysis - Lu Tian; Siyu Yang; Yulan Hu; Jinrui Cui; Xiaobei Guo; Zongfeng Liao; Yu Liu (Health Science Reports)
ABSTRACT Aims The question of how to choose the right type of exercise to lower blood pressure and cardiovascular risk factors in people worldwide with high blood pressure is not yet fully understood. Thus, the aim of this study was to investigate the effects of various exercise training on blood pressure and cardiovascular risk factors among young and middle‐aged adults with prehypertension or hypertension. Design Systematic review and network meta‐analysis. Methods We searched five electronic databases to identify randomized controlled trials that compare exercise training versus a sedentary or sham control group in young and middle‐aged adults with prehypertension or hypertension. Review Manager 5.3, Stata15.0, and R4.2.1 software estimated the efficacy of exercise training modalities. Results We included 19 eligible articles with 1590 participants to assess five exercise trainings. Our findings indicated that low‐middle intensity aerobic exercise (mean difference (MD) = −8.08, 95% confidence interval (CI) = −13.58, −2.58) was superior to all exercise strategies (high‐intensity aerobic exercise: MD = −6.53, 95% CI = −12.51, −0.56; high‐intensity resistance exercise: MD = −4.95, 95% CI = −11.07, 1.17; low‐middle‐intensity resistance exercise: MD = −3.49, 95% CI = −12.36, 5.39) compared with control group in lowering systolic blood pressure. Compared with the control strategy, high‐intensity resistance exercise (MD = −4.75, 95% CI = −8.00, −1.50), high‐intensity aerobic exercise (MD = −4.27, 95% CI = −7.08, −1.45) could lower diastolic blood pressure. The effects of different exercise patterns on cardiovascular risk factors, the results indicated that only low‐middle‐intensity aerobic exercise significantly improved body mass index (MD = −0.55, 95% CI = −7.08, −1.45), total cholesterol (MD = −19.07, 95% CI = −36.42, −1.72), triglycerides (MD = −14.32, 95% CI = −23.16, −5.48), high‐density lipoprotein (MD = 2.29, 95% CI = 0.85, 3.73), and low‐density lipoprotein (MD = −13.90, 95% CI = −22.18, −5.63). In addition, no intervention affects heart rate. Conclusion Compared with other types of exercise, aerobic exercise can significantly improve systolic blood pressure, while high‐intensity resistance or aerobic exercise may significantly improve diastolic blood pressure. In addition, AE‐LM is effective in the reduction of risk factors that are contributors to the development of cardiovascular disease. Therefore, this study provides strong evidence to support the selection of appropriate exercise modalities for hypertensive patients.